Collaborative Design Pedagogy (CDP) for Cultivating Student-Centered Learning (SCL) in a hybrid architecture design studio during the endemic phase / Alice Sabrina Ismail, Azalilah Ramdani Musa, and Shahariah Norain Shaharuddin - Ismail, Alice Sabrina; Musa, Azalilah Ramdani; Shaharuddin, Shahariah Norain (Universiti Teknologi MARA, Perak, 2023)
Architecture education is unique because the architectural education system is project-based learning, where the primary teaching and learning process occurs within the studio. However, during the endemic phase, architecture studios are conducted in a hybrid manner in which the learning process for architecture design faces many challenges.This includes exposing and testing students' ability to combine knowledge from disciplines such as philosophy, art, sociocultural, management, science and technology whilst nurturing student-centred learning within a hybrid environment. This paper elucidates how student-centred learning (SCL) is emphasized and implemented in a hybrid architecture design studio during the endemic phase using Collaborative Design Pedagogy (CDP). This paper is significant as it will showcase the practical approaches and successful methods done by the UTM Architecture program in applying the CDP framework for a hybrid architecture design studio that led to the recognition by the Board of Architect Malaysia (LAM) in the year 2022 for the program to gain five years full accreditation until the year 2026. The paper outcome will be presented as a CDP framework module specifically on conducting a hybrid architecture design studio that promotes SCL as an example for other architecture schools to refer to for future lifelong architecture learning. The CDP framework is also beneficial as it highlights the flexibility to be adopted as a non-conventional architectural learning strategy that can lead to nurturing creative thinking among architecture students.